The Kerala Tourism Model – An Indian State on the Road to Sustainable Development. (31st March 2016) - Thimm, Tatjana
Abstract: Sustainable tourism in Kerala is on the rise. Therefore, this South Indian state is assessed according to the sustainable tourism criteria of the Strasdas et al. (2007) framework. Kerala as a state does not qualify as a sustainable tourism destination, although individual success stories at the NGO and government level exist. This conceptual paper delivers a detailed analysis of the three dimensions of sustainability, i.e. ecology, economy and socio‐cultural aspects, of the 'Kerala tourism model' and discusses the question of whether this model can be transferred to other developing countries. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment